Post-Coronary Artery Bypass Medications in Dialysis Patients: Do We Need to Change Strategies? - Hu, Yu-Ning; Luo, Chwan-Yau; Tsai, Meng-Ta; Lin, Ting-Wei; Kan, Chung-Dann; Roan, Jun-Neng (The Thoracic and Cardiovascular Surgeon, 2019)
Background Coronary artery bypass grafting (CABG) is frequently performed in patients with end-stage renal disease (ESRD) together with severe coronary artery disease, after which, patients with ESRD have higher surgical risk and poorer long-term outcomes. We report our experience in patients with ESRD who survived in CABG and identify predictors of long-term outcomes.Methods We retrospectively investigated 93 consecutive patients with ESRD who survived to discharge after isolated CABG between January 2005 and December 2016 at our institution. Long-term outcomes, including all-cause mortality after discharge, readmission due to major adverse cardiac events, and reintervention, were evaluated. Predictors affecting long-term outcomes were also analyzed.Results The rates of freedom from all-cause mortality after discharge in 1, 3, 5, and 10 years were 92.1, 81.3, 71.9, and 34.9%, respectively. The rates of freedom from readmission due to major adverse cardiac events in 1, 3, 5, and 10 years were 90.7, 79.1, 69.9, and 55.6%, respectively. The rates of freedom from reintervention in 1, 3, 5, and 10 years were 95.3, 86.5, 79.0, and 66.6%, respectively. Postoperative β-blocker and statin use significantly improved overall long-term survival (β-blocker, p = 0.013; statin, p = 0.009). After case–control matching, patients who received statins showed better long-term survival than those without statins. The comparison of long-term survival between patients with and without β-blockers showed no significant difference after matching.Conclusions After CABG, dialysis patients who survived to discharge had acceptable long-term overall survival. Post-CABG statin use in dialysis patients is a predictor of better long-term survival.
Keywords: coronary artery bypass grafts surgery; CABG; ischemic heart disease; angina